WESTERN PSYCHOLOGY AND ISLAMIC PSYCHOLOGY IN DIALOGUE; COMPARISONS BETWEEN ISLAMIC THEORY AND WESTERN THEORY OF PERSONALITY - Sudirman, Subhan Ajrin (Al-Qalb : Jurnal Psikologi Islam, 2017)
In the mid-1960s, humanistic psychological figures such as Abraham Maslow, Antonio Sutich, Charles Tart, Stanislav Grof began to reconsider the dimensions of spirituality and the object of ontology-metaphysical into the field of psychological research. By opening up to a spiritual experience and adopting it into the discipline of psychology through therapeutic techniques. They view that the perspective of modern psychology tends to be partial-particular, so that in its implementation it is often unable to cope with the full humanitarian crisis. As the teachings of monotheism, Islam certainly emphasizes the importance of the foundation of monotheism in all its dimensions, including in it concerning the systematics of thought associated with the religious dimension. This concept is also the main foundation for the principles of epistimology in Islam, as well as the principle of unifying and strengthening the integration of science. So the allegation that Islamic psychology has no epistymological foundation is an unfounded claim, apt to be ahistorical and a priori.